Constantijn Huygens and his ‘East Indian Writing Tray’ - Jongstra, Jaap; van Campen, Jan (The Rijksmuseum Bulletin, 2023)
Jaap Jongstra and Jan van Campen describe a letter from Constantijn Huygens from 1629 in which he asks a supplier to provide a writing tray made of red lacquer, exactly like the one he already possessed. Objects with red lacquer were still very rare at that time. Some other objects from Huygens' collection are now housed in the Rijksmuseum.